Case of anterior glottic web with bilateral vocal cord cancers. Issue 9 (6th September 2022) - Kusunoki, Takeshi; Wada, Ryo
Abstract : We experienced a case of anterior glottic web with bilateral vocal cord cancers. The laryngoscopic findings showed milky tumour lesions on bilateral vocal cords and a web-like formation with an adhesion in the anterior commissure. In this case, we performed laryngomicrosurgery to remove the bilateral vocal cord tumours and the anterior glottic web. This case was diagnosed as bilateral glottic carcinoma (laryngeal carcinoma TNM classification: pT1bN0M0) with an anterior glottic web. Therefore, this patient underwent radiation therapy (66 Gy). At present, one and a half years have passed since the end of radiotherapy. There is no recurrence of the glottic cancer or web. The airway at the glottis was patent. It has been reported that cutting-off the anterior glottic web could easily lead to readhesion. Accordingly, we continued to follow-up to determine whether there was a recurrence of readhesion of the anterior glottic web or glottic cancer.